Analisa Daya Dukung Gardu Traksi Kranji Pada Pengoperasian Kereta Bandara Soekarno - Hatta - Wicaksono, Catur; Akhwan, Akhwan; Putri, Ava Rizkinda (Politeknik Perkeretaapian Indonesia Madiun, 2018)
This research was prepared with the aim of carrying out the calculation of the capacity of the traction substation and analyzing the carrying capacity of the Kranji Traction Substation at the operation of the Soekarno-Hatta Airport Train at rush hour in the morning. This research was conducted with data sources in the form of a train circuit arrangement, filling distance between traction substations, headway, double track type, train consumption ratio, and total train weight. The capability parameters of the substation carrying capacity are measured based on the narrowing of the 8.5 minute, 5 minute and 3 minute headway and the blackout of the Cakung substation. The plan load value is obtained based on the ratio of the maximum current load to the headway constriction load. Carrying capacity is measured based on the comparison of planned load values ​​to the existing capacity of substations. The results of the analysis stated the rectifier load was 2626.42 kW and the transformer load was 3533 kVA on all types of parameters. With a rectifier capacity of 43% and a transformer of 51%. An evaluation of the results of the data analysis showed that the Kranji Traction Station was able to supply power for the operation of the Soekarno-Hatta Airport Train in the morning rush hour.